Optimalisasi Sistem Informasi Puskesmas pada Layanan Kesehatan di Puskesmas Dlingo I Kabupaten Bantul Yogyakarta - Nur Rokhman; Savitri Citra Budi; Nuryati Nuryati (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2015)
Dlingo I Community Health Center used Integrated Health Information System (IHIS) as software to support patient services. Besides IHIS, Dlingo I Community Health Center also used P-Care to records data service of BPJS patients. There are some technical problems related to the use of IHIS and P-Care. Community service has been held in Dlingo I Community Health Center to give a training and assistance for the officers. In early stage we analyzed the problems and the needs of Dlingo I Community Health Center officers with observation and interview. Some problems has been found like the lack of responsiveness of P-Care and the server that temporary down. There are also some feature in IHIS that didn’t meet the officer expectation. From the problems mentioned above, Vocational College of Universitas Gadjah Mada held a training and assistance related to the use of P-Care and IHIS. As an output from this activity we also make a recommendation for the development of community health center information system in the future. The officers claimed that they are satisfied with the training and the assistance.